Desain Physics Brain: Aplikasi Pembelajaran Kinematika Gerak untuk Meningkatkan Kemampuan Berpikir Kritis Dan Literasi Sains Siswa SMA - Annisa Khoirul Hidayati; Najla Adristi Listyowati; Bayu Setiaji (LPPM UNIVERSITAS PGRI SILAMPARI, 2023)
This study aims to determine the feasibility of the Physics Brain application as an android-based learning media to improve critical thinking and scientific literacy skill in the developed physics lesson. The Physics Brain application contains material, sample questions, and quizzes that are packaged as attractive as possible. The research method used was the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Research on the development of the ADDIE model was carried out only in Analysis, Design, Development, and Evaluation. This study uses a Likert scale analysis technique. The results of the research showed that the practitioner validator and respondent stated that the learning media design developed obtained an overall percentage value of 85% and was included in the very feasible category so that the Physics Brain application could be used in learning.